Development of elliptic core-shell nanoparticles with fluorinated surfactants for 19F MRI - Wu, Yue; Minoshima, Masafumi; Kikuchi, Kazuya (Frontiers in Chemistry, 2024)
Perfluorocarbon-encapsulated silica nanoparticles possess attractive features such as biological inertness and favorable colloidal properties for bioimaging with fluorine magnetic resonance imaging (19F MRI). Herein, a series of elliptic shaped silica nanoparticles with perfluorocarbon liquid perfluoro-15-crown-5 ether as core (PFCE@SiO2) were synthesized using fluorinated surfactants N-(perfluorononylmethyl)-N,N,N-trimethylammonium chloride (C10-TAC) and N-(perfluoroheptylmethyl)-N,N,N-trimethylammonium chloride (C8-TAC). The nanoparticles are characterized to obtain elliptic core-shell structures. PFCE@SiO2 showed strong 19F NMR signals of the encapsulated PFCE, indicating the potential as a highly sensitive 19F MRI probe. These elliptic PFCE@SiO2 nanoparticles provide a new option of 19F MRI probe with a morphology different from conventional nanospheres.